Design of Tele-Consultation for Pediatric Cardiology Service in Mobile Clinics at Our Institution - Mohanageetha Ardhanari; Lisa Gwynn; Richard E. Kardon; Mary C. Sokoloski (Telemedicine Reports)
Background: The establishment of tele-cardiology in mobile clinics improves patient access to pediatric cardiology service in remote locations. Objectives: The aim of this article is to describe the design of tele-consultation for pediatric cardiology in mobile clinics at our institution. Materials and Methods: Patients with limited healthcare access presenting to community pediatric mobile clinics for care are evaluated by a pediatrician in the field. Those patients with findings warranting cardiac evaluation return for tele-cardiology consultation. Consultation takes place in a portable tele-clinic system on mobile unit equipped with encounter management software, customized medical devices, and videoconferencing. At tertiary center, a broadband-enabled computer with videoconferencing software allows for real-time tele-cardiology consultation. Videoconferencing, tele-auscultation, tele-electrocardiography, and tele-echocardiography are incorporated into the evaluation to replicate an outpatient cardiology evaluation. Results: Since establishment of tele-echocardiography at our institution, 30 patients have undergone tele-cardiology consultation including a screening echocardiogram. Patients ranged from 4 to 19 years age (mean: 9.6 years). Indications for referral were cardiac murmur (n = 14), chest pain (n = 4), syncope (n = 2), high blood pressure (n = 2), atrial septal defect (n = 1), patent foramen ovale (n = 1), ventricular septal defect (n = 2), and VATERL association (n = 1). Structural anomalies were detected in 6 patients: patent foramen ovale (n = 1), secundum atrial septal defect (n = 1), aortic regurgitation (n = 1), aneurysmal septum primum (n = 1), and ventricular septal defect (n = 2). Two patients were referred for in-person cardiac evaluation for potential intervention: secundum atrial septal defect and aortic regurgitation. Conclusion: Tele-consultation for pediatric cardiology with a smooth workflow is successfully established in mobile clinics at our institution.